Pengaruh Locus of Control Dan Stres Kerja Terhadap Kinerja Dosen Akademi Kebidanan - Anah Sugihanawati (SEAJOM: The Southeast Asia Journal of Midwifery, 2019)
Professional midwives are produced from a good midwives education. Good midwives ' education requires a good mentor or lecturer. Some data were found that the lecturers ' performance in obstetrics academy in indonesia is still a challenge especially in general performance or special performance in conducting high school tridarma. The study wanted to know the effects of locus of control and work stress on performance. This research is a quantitative study with analysis survey method of 108 obstetrician academy lecturers in dki jakarta area. respondents are randomly selected. inferential statistics are used to test hypotheses about the influence between variables using pathway analysis techniques. The results showed that locus of control was a direct positive effect on performance; occupational stress is a direct negative effect on performance, and locus of control directly negatively affects the stress of work. research results can help in improving performance through improved locus control and lower working stress on obstetrics lecturers.